2020
DOI: 10.1007/s40194-020-00881-8
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of welding stresses on relief cracking during heat treatment of a creep-resistant 13CrMoV steel Part II: mechanisms of stress relief cracking during post weld heat treatment

Abstract: Welding of 13CrMoV9-10 vanadium steel requires care due to an increased susceptibility to stress relief cracking during post weld heat treatment. Previous research into the crack formation in creep-resistant steels has focused on thermal and metallurgical factors; however, little knowledge has been gathered regarding the crack formation during post weld heat treatment considering real-life restraint conditions. This work is subdivided in two parts. Part I showed that an increasing heat input during submerged a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This can be intensified due to external restraints or other phenomena like the hydrogen assisted cracking [ 25 , 26 ]. Stress relief cracking Cracking which occurs due to high strength and low ductility during post weld heat treatment [ 27 , 28 , 29 ]. Pore formation Pore formation occurs mostly due to a gap in the solubility of gases between the solid material and the melt [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be intensified due to external restraints or other phenomena like the hydrogen assisted cracking [ 25 , 26 ]. Stress relief cracking Cracking which occurs due to high strength and low ductility during post weld heat treatment [ 27 , 28 , 29 ]. Pore formation Pore formation occurs mostly due to a gap in the solubility of gases between the solid material and the melt [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cracking which occurs due to high strength and low ductility during post weld heat treatment [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the BWI, API, and Lehigh 2015 tests, it applies a tensile load to the test sample on heating, aiming to replicate the effect welding residual stresses have on carbide precipitation and SRC susceptibility before reaching the PWHT temperature. It was shown that heating under tensile load affects the carbide precipitation mechanism [19] and may cause SRC failures in highly susceptible materials, which was experienced both in this work and in previous research [12]. Compared to the Lehigh 2000 and OSU 2014 procedures, the controlled straining on heating to PWHT temperature compensates the effect of thermal expansion on the applied tensile load and allows evaluating the effect of residual stress level on SRC susceptibility.…”
Section: Discussionmentioning
confidence: 73%
“…The grain boundary strain accumulation results from grain interior strengthening by precipitation of secondary carbides [2,3,6,23,26]. It was demonstrated that carbide precipitation in Cr-Mo steels is a fast process that can initiate heating during PWHT [14,19]. Grain boundary embrittlement results from diffusion-controlled segregation of impurities and tramp elements and precipitation of coarse carbides [2,3,6].…”
Section: Discussionmentioning
confidence: 99%
“…The denser electron flow and prolonged local heat in the welding lead to higher dilution of the fusion zone, which means a wider weld bead [14]. Higher heat input caused higher internal stresses [14,15]. Higher internal stresses can cause lower mechanical properties [16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%